Primary erythromelalgia mainly manifested by hypertensive crisis: A case report and literature review - Feng, Shuo; He, Zhanwen; Que, Liping; Luo, Xiangyang; Liang, Liyang; Li, Dongfang; Qin, Lijun (Frontiers in Pediatrics, 2022)
Background Primary erythrocytic (PEM) is a rare autosomal dominant single gene disease. Most of the changes of gene loci can be found by whole exon gene sequencing, and the clinical symptoms and patient survival can be improved by specific site-to-site drug treatment. The other manifestations of this patient population are not remarkable. After the application of common drugs, the toxicity and side effects can be limiting. In addition to other common clinical manifestations, we found that the only unique manifestation of this patient was hypertensive crisis. Following multidisciplinary diagnosis and treatment (MDT), we decided to first control hypertension to alleviate the acute and critical patients. However, after controlling the hypertensive crisis, we unexpectedly found that the clinical symptoms of the patients had been significantly improved. Therefore, we concluded that the use of antihypertensive drugs can treat erythematous limb pain with the clinical manifestation of hypertensive crisis. Here, we describe a typical PEM disease, primary clinical features, diagnosis and treatment. Methods Medical records of an 8-year-old boy with PEM were analyzed retrospectively, which included clinical characteristics, follow-up information, and SCN9A (Sodium Voltage-Gated Channel Alpha Subunit 9) gene analysis. Results The 8-year-old boy had complained of abnormal paresthesia in his feet and ankles with burning sensation and pain for 2 years. The skin of both lower legs was red and underwent ichthyosis and lichenification. Genetic analysis confirmed the existence of a SCN9A gene mutation. The symptoms were gradually improved by treating with intravenous drip and oral administration of nitroglycerin to slow his heart rhythm. Conclusion Primary erythrocytic is characterized by skin ulceration, redness, elevated temperature, and severe burning pain primarily in both lower extremities. PEM can be diagnosed by genetic analysis. As this case demonstrates, treating with nitroglycerin as the drug of choice to control the hypertensive crisis significantly improved the symptoms of PEM and hypertension in this patient.